Vallejo and Agamben: The potency of the new word - Quenaya, Carlos (2019)
This work will follow Italian philosopher Giorgio Agamben to explore, based on his «poetics of the inoperative», the epistemology of Trilce (1922). I will try, then, to expose how the critical reception of Vallejo’s work coincides with the political and aesthetical work of Agamben. Simultaneously, I will suggest the epistemic and political alternatives that are present in Trilce, with the aim of broading the framework of the Agambenian reflection. As a critique of the metaphysical conceptualization of language, Trilce would qualify as an excellent case in which the language’s potency is manifest. By appealing to new readers, Trilce’s performative force represents a new beginning, an event that responds to the novelty of its new word.